How can Electronic Medical Record Help improve Health Services in Emirate of Abu Dhabi? - Al Musabi, Mona (2010)
Health Information System is the current most widely discussed topic in Abu Dhabi hospitals; as the implementation of such a system is still being rolled out to all hospitals and primary health care centers; also, let us consider the fact that those kinds of implementations are relatively new in the Middle East area. How to improve it? Or what are the lessons learnt?This Thesis consist of 5 chapters that discuss how other authors in other countries have discussed how their HIS or EMR implementations have benefited the organizations; challenges associated with those implementations and how to overcome them in the future for better practice.To get a sense of reality check; I have conducted a survey in a number of hospitals and clinics; there’s a whole chapter that discuss the survey analysis and findings with regards to HIS implementation in Abu Dhabi